Proneness to Space-Related Learning and Behaviour in the Spot of Neurological-Evolutionary Determinants (I) - Köck, Helmuth (Journal of Geography Education, 2005)
To explain proneness to space-related learning and behaviour, sociocultural factors like, for instance, age, gender, marks are pulled up. That space-related proneness is, however, in first line caused evolutionary-neurologically, does hardly play a role in geographic-didactic research so far. With this background, this article tries to explain some cognitive and affective effects of space-related learning and behaviour by falling back on neurological and evolutionary influencing factors as well as marking their role as obstacle or as potential.